Power to the Principals: Decentralization in Three Large School Districts - Ouchi, William G. (Organization Science, 2006)
School districts have made several attempts at decentralizing. However, decentralization in school districts can mean so many different things that the term has nearly lost its meaning. This paper reports a study of three large urban school districts that, over almost 30 years, adopted nearly identical approaches to decentralizing, granting control to principals and expanding freedom of choice for families. In all three cases, the goal of improving student achievement was achieved, although with a very small sample. These three districts are compared to the three largest public districts in North America. The comparisons reveal that the three decentralized districts attained a high level of principal control over school budgets, staffing, schedule, and teaching methods.